Pengaruh Tunjangan Kinerja Daerah Terhadap Kinerja Aparatur Sipil Negara Dinas Pekerjaan Umum dan Penataan Ruang Kota Cimahi - Novianti Chintia Dewi; Mia Rosmiati (Indonesian Accounting Research Journal, 2022)
This study aims to determine the effect of regional performance allowances to the performance of civil servant in Public Works And Spatial Planning Department Of Cimahi City. The data collection methods used in this study are questionnaire distributed to 43 state civil servants and documentation using documents related to this research. The method of data analysis in this study is simple linear regression using the IBM SPSS Version 25 statistical program. The results of this study indicate that the regional performance allowance has a positive effect on the performance of civil servant. This is indicated by the coefficient of determination (R Square) that the regional performance allowance has an effect of 47.5% on the performance of civil servant and the remaining 52.5% is influenced by other factors not examined. Then, the relationship of the regional performance allowance variable to the performance of civil servant in the form of a regression equation is Y = 8.965 + 0.811X.